REKONSTRUKSI PEMIKIRAN FIKIH: Suatu Gagasan Awal Mencairkan Kebekuan Fikih di Indonesia - Mustafa, Muhtadin Dg. (State Institute of Islamic Studies (IAIN) Palu, 2011)
Indonesia is a country whose population is majority Muslim. Thus, the aspects of syari’ah (Islamic law) should color the religiousity of Indonesian Muslims. However, the syari'ah is not static, it is dinamic as it always gets in contact with social aspects. In this context, the reactualization and reconstruction of Islamic jurisprudence should be continually performed. The reactualization of the Islamic jurisprudence related to pragmatic values covering the patterns of daily life of the Muslims while the reconstruction the Islamic jurisprudence thought more focuses on conceptual intellectuality values. Based on the relationship of the idea of reactualization and reconstruction of the Islamic jurisprudence, it can be concluded that the latter is an infrastructure, while the renewal is a means to realize the function of syari'ah (Islamic law) as a social control and social engineering.